Application of Smart City Construction in a New Data Environment - Yunhong Zhao; Suruo Li; Huafeng Chen; Yuhua Xu (Frontiers in Energy Research, 2022)
With the rapid development in the internet, cloud computing, Internet of Things, mobile internet, and other information technologies, the big data technology is widely used in all aspects of smart city construction. This study analyzes the development status of big data in urban planning and construction and studies the application of the big data technology in smart city construction. This study mainly analyzes and studies the aspects of smart city planning, smart transportation, smart community, smart health care, and smart education and finally puts forward relevant thoughts.